Management of Perforation Injuries During and Following Penile Prosthesis Surgery. (November 2015) - Stember, Doron S.; Kohler, Tobias S.; Morey, Allen F.
Abstract: Introduction: Distal extrusion of penile prosthesis cylinders is a challenging problem that is associated with pain and imminent erosion through penile skin. Distal extrusion and other perforation injuries, including crural and urethral, are other manifestations of tunica albuginea injuries that result in poor clinical outcomes and patient satisfaction. Aim: A description of Dr. John Mulcahy's landmark article for management of lateral extrusion is presented along with discussion of techniques for managing other types of perforation injuries associated with penile implants. Methods: Dr. Mulcahy's original article is reviewed and critiqued. Surgical methods to manage perforation injuries are discussed. Main Outcomes Measures: The main outcome measures used were the review of original article, subsequent articles, and commentary by Dr. Mulcahy. Results: Knowledge of techniques for management intraoperative and postoperative complications related to tunical perforation is necessary for implant surgeons. Conclusions: Perforation injuries are challenging noninfectious complications of penile prosthesis surgery. Familiarity with techniques to manage these problems is essential for ensuring good outcomes and patient satisfaction.Stember DS, Kohler TS, Morey AF. Management of perforation injuries during and following penile prosthesis surgery. J Sex Med 2015;12(suppl 7):456–461.